Revision of the New Zealand species of the Genus Pselaphaulax Reitter (Staphylinidae: Pselaphinae: Pselaphitae: Pselaphini) - Owens, Brittany E.; Carlton, Christopher E. (Zootaxa, 2022)
In New Zealand, the genus Pselaphaulax Reitter is represented by thirteen species. Six new species are described: Pselaphaulax hornabrooki Owens and Carlton, sp. nov.; Pselaphaulax intermedius Owens and Carlton, sp. nov., Pselaphaulax nunni Owens and Carlton, sp. nov.; Pselaphaulax pelorus Owens and Carlton, sp. nov.; Pselaphaulax ramsayi Owens and Carlton, sp. nov.; and Pselaphaulax tararua Owens and Carlton, sp. nov. Pselaphus trifoveatus Broun, 1914 is synonymized under Pselaphus pilifrons Broun, 1914 syn. nov. and is transferred to Pselaphaulax comb. nov. Two species, Pselaphus pilistriatus Broun, 1880 and Pselaphus fuscopilus Broun, 1886 are synonymized under Pselaphus pauper Sharp syn. nov., which is also transferred to Pselaphaulax comb. nov. Pselaphus meliusculus Broun, 1893 is also transferred to Pselaphaulax comb. nov. Lectotypes and paralectotypes are designated for the Broun and Sharp species. Distributional maps and line drawings of diagnostic characters for each species are provided. A regional checklist and key are provided to species of the genus that occur in New Zealand.